(untitled) (Research, Society and Development, 2021)
The obstruction of the airways by foreign bodies is considered a serious and potentially fatal accident that can occur at any stage of life, because of this, it is essential that the mothers or guardians have knowledge about first aid from the prenatal period, so that , at birth, already possess knowledge on the subject, as the need for immediate intervention arises, thus increasing the probability of survival. The present study aims to analyze the knowledge of postpartum women related to first aid when faced with airway obstruction caused by a foreign body in newborns. This is a study with a quantitative approach, of a descriptive nature, which was carried out in a reference maternity hospital in the Northeast. Data collection was carried out in one of the maternity wards, consisting of 10 beds, two of which were disabled and took place through a semi-structured questionnaire, from August to September 2021, with the mothers who were in the postpartum period. corresponding to 24h-48h. The final sample consisted of 100 postpartum women. They had a satisfactory level of knowledge on the subject, however the health services have a fundamental role in the dissemination of this information.